2020
DOI: 10.1177/2150132720958832
|View full text |Cite
|
Sign up to set email alerts
|

Understanding User Acceptance of Clinical Decision Support Systems to Promote Increased Cancer Screening Rates in a Primary Care Practice

Abstract: Objective: Clinical decision support systems (CDDSs) in the electronic medical record (EMR) have been implemented in primary care settings to identify patients due for cancer screening tests, while functioning as a real time reminder system. There is little known about primary care providers (PCPs) perspective or user acceptance of CDSS. The purpose of this study was to investigate primary care provider perceptions of utilizing CDSS alerts in the EMR to promote increased screening rates for breast cancer, cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 49 publications
0
6
0
1
Order By: Relevance
“…The review also acknowledged barriers to implementation, including physician mistrust in the tool, disagreement with the recommendation and guidelines embedded within the tool, and interruption to clinical workflow 30 -similar to the themes found in this focus group study and also confirmed by other studies with providers regarding their views on implementing these tools in primary care, together with the worry of alert fatigue and burden for the end-users. 31,32 Shah et al implemented an EHR-based-algorithm for riskstratified prostate cancer screening in a primary care network of 300 clinicians at 40 sites in North Carolina and compared pre-versus postimplementation outcomes. The algorithm was based on a mix of national guidelines (USPSTF, NCCN, American Cancer Society).…”
Section: Discussionmentioning
confidence: 99%
“…The review also acknowledged barriers to implementation, including physician mistrust in the tool, disagreement with the recommendation and guidelines embedded within the tool, and interruption to clinical workflow 30 -similar to the themes found in this focus group study and also confirmed by other studies with providers regarding their views on implementing these tools in primary care, together with the worry of alert fatigue and burden for the end-users. 31,32 Shah et al implemented an EHR-based-algorithm for riskstratified prostate cancer screening in a primary care network of 300 clinicians at 40 sites in North Carolina and compared pre-versus postimplementation outcomes. The algorithm was based on a mix of national guidelines (USPSTF, NCCN, American Cancer Society).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of 37 PCCs practicing in another Midwestern healthcare system found that most PCCs were comfortable using CDS system alerts for patients overdue for cancer prevention and screening, but that compared to physicians, advanced practice clinicians (e.g., nurse practitioners and physician assistants) had significantly higher rates of agreeing that CDS system alerts were straightforward, the current number of alerts was acceptable, and that more alerts were needed [33]. While the present study did not compare post-implementation responses by PCC type, we reported a similar comparison between PCC types pre-implementation [4], with few significant differences seen between physicians and advanced practice clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Kingdom for other disease areas such as stroke, cancer, cystic fibrosis, and dementia [23][24][25][26][27][28]. For example, in the United Kingdom, a national stroke registry has transformed patient care and outcomes, with early recognition of different patterns of stroke presentation, focused treatment on previously untreated risk factors, and targeted interventions for improving cognitive impairment [27].…”
Section: Digital Registries Have Been Deployed Successfully In the Un...mentioning
confidence: 99%